HUBUNGAN KEKUATAN OTOT LENGAN DAN KESEIMBANGANSTATISDENGAN JAUHNYA LEMPARAN TURBO - Adi Suriatno; Rusdiana Yusuf (JUPE : Jurnal Pendidikan Mandala, 2019)
This study aims to determine whether there is a Relationship of Muscle Arm Strength And Stainless Equilibrium With Turbo Shot Deep In "The population of this study using all with the number of research samples as many as 25 people so this research uses population study techniques. The data collection technique is using the test method of deed and documentation. Arm muscle strength instruments are Push Up, static balance using a stork stand, and turbo throw using 2 turbo. Technique of data analysis using double correlation method, from result of research at 5% significant level stated that there is relation of arm muscle strength with throw away turbo where the value of r value count bigger than r table (0,617> 0,396), So the final result of this research is no relationship Arm Muscle Strength and Static Balance with Remote Turbo Shot on Lesson Year 2019.